Strategic Management of Madrasah Heads in Improving The Quality of Language Learning Arabic in Islamic Educational Institutions - Susanti, Riri; Tariq, Kubota; Carmelo, Dumaz (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Language problems are difficulties that students face when learning elements of the target language. Based on this fact, there is a premise that learning a foreign language is easy or not depending on the systematic comparison between the student's language and the target language. Purpose. This study aims to find out that the existence of teachers is the main actor who acts as a facilitator in the learning process for students. Therefore, their existence and professionalism are very influential on the achievement of national education programs. Method. The method used by researchers is quantitative method, this quantitative research can show data containing numbers that can be obtained by utilizing micro components of the education system in schools as a means that can be used by researchers as the subject of their research. Results. The madrasah principal and teachers are one of the components that are very decisive for the implementation of education. Teachers are the main actors who act as facilitators in the learning process for students. Teachers must be qualified because they are one of the micro components of the education system in schools. Conclusion. it is very important for madrasah principals to improve the quality of Arabic language learning. Teachers must be qualified because teachers are one of the micro-components of the school education system. Therefore, it is very important for madrasah principals to improve the quality of Arabic language learning.